THE INDONESIAN TRANSLATION OF ENGLISH SEXUAL EUPHEMISTIC EXPRESSIONS IN DESPERATE DUCHESSES BY ELOISA JAMES - Anita Anita; M. R. Nababan; Riyadi Santosa; Agus Hari Wibowo (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
Translation cannot be separated from culture; therefore, a translator must have sufficient knowledge about the culture of the language that is going to be translated. This knowledge will help the translator to determine the most suitable equivalent of any text containing cultural elements. Euphemism is one of the texts. Euphemism is used to replace an expression that considered threatening the face of the speaker, the audience or some third party when it is uttered. Sex is the topic that will offend people when it is talked about openly. People in every culture tend to use euphemism when they talk about sex. However, different culture will see sex with different point of view.  This study aims to find out the differences through the translation of English sexual euphemistic expression into Indonesian. It will describe how those expressions are translated into Indonesian. This study is a descriptive qualitative study. The source of the data is an English novel by Eloisa James entitled Desperate Duchesses and its Indonesian version Memikat Kekasih. The result shows that English sexual euphemistic expressions in the novel are translated into Indonesian euphemisms, Indonesian dysphemisms, literal meaning, and description.